Decomposing the Drivers of Changes in Inequality During the Great Recession in Ireland using the Fields Approach - O’Donoghue, Cathal; Loughrey, Jason; Sologon, Denisa M. (The Economic and Social Review, 2018)
In this paper we take as a case study a developed country that both experienced one of the highest sustained growth periods in recent decades, but also had one of the largest economic declines during the recent crisis period; Ireland. In particular, given the availability of data and the period from the peak before the economic crisis and the lowest point in the crisis, we focus on the period around the boom 2007-2012. We find that inequality in terms of disposable income decreased over the period, with an increase in the redistributive effect of the tax-benefit system offsetting a rise in market income inequality. We utilise the Fields regression decomposition to understand the impact of demographic, labour market and other drivers. We find that the explanatory power of the Fields regressions fell over time, reflecting the asymmetric shock induced by the economic crisis. Labour market drivers had the largest impact on the level of income inequality over the period, accounting for 64 per cent of variability in 2007, but rising to 75 per cent in 2012. Educational attainment is positively associated with inequality. However, the effect greatly diminished between 2007 and 2012. Changes in the demographic structure and changes in the level and distribution of market incomes increased inequality. We also decomposed the change in inequality into price and quantity effects that result from a change in the return and composition respectively.